Telomere & Early Senescence Trophoblast in Preeclampsia: Impact & Opportunity - Prof. Adhi Pribadi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
In general, and with numerous studies, telomeres in trophoblast cells tend to be significantly shorter in preeclampsia compared to normal pregnancies. This telomere shortening occurs due to high oxidative stress and premature cellular senescence in the placenta.What are Telomeres? Telomeres are the final sections of chromosomes, consisting of repeating DNA strands. Telomeres function as protective